Media Culture and Media Education in Ensuring the Modernization of Higher Education System in Uzbekistan - Ablazov Elyorbek Erkinjonovich (Research Parks Publishers, 2022)
The article is devoted to the practical implementation of the synthesis of media criticism and media education in the learning process of pupils and students in Uzbekistan. The author indicated the fields of media criticism in the modern media landscape of these countries. The author analyzed the main directions and trends of media criticism and media education, leading media critics and the media.